Combining Two Methods of Sequence Definition in a Convergent Approach: Scalable Synthesis of Highly Defined and Multifunctionalized Macromolecules. Issue 56 (8th September 2017) - Solleder, Susanne C.; Martens, Steven; Espeel, Pieter; Du Prez, Filip; Meier, Michael A. R.
Abstract: The straightforward convergent synthesis of sequence‐defined and multifunctionalized macromolecules is described herein. The first combination of two efficient approaches for the synthesis of sequence‐defined macromolecules is reported: thiolactone chemistry and the Passerini three‐component reaction (P‐3CR). The thiolactone moiety was used as protecting group for the thiol, allowing the synthesis of a library of sequence‐defined α, ω‐functionalized building blocks. These building blocks were subsequently efficiently coupled to oligomers with carboxylic acid functionalities in a P‐3CR. Thus, larger oligomers with molecular weights of up to 4629.73 g mol −1 were obtained in gram quantities in a convergent approach along with the introduction of independently selectable side chains (up to 15), thus clearly demonstrating the high versatility and the efficiency of the reported approach. Abstract : Little by little : The first combination of efficient thiolactone chemistry and the Passerini three‐component reaction (P‐3CR) for the synthesis of sequence‐defined macromolecules is reported. The thiolactone moiety was used as protecting group for the thiol, allowing the synthesis of a library of sequence‐defined α, ω‐functionalized building blocks. These building blocks were subsequently coupled to oligomers to give larger oligomers with molecular weights of up to 4629.73 g mol −1 in gram quantities with up to 15 independently selectable side chains.